HUBUNGAN TINGKAT KEMANDIRIAN DENGAN RISIKO JATUH PADA LANSIA DI PANTI WERDHA DARMA BHAKTI KM 7 PALEMBANG - Sari, Wayan Super Sekar; Indaryati, Sri; Nurjanah, Vausta (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
The risk of falling is easily exsperienced by the elderly. One of the factors that affect the risk of falling in the elderly is a musculoskeletal system disorder such as a walking disorder due to muscle weakness and joint stiffness. Elderly who live in nursing homes are more likely to fall than those who live at home with their family. This isi because the elderly who live in nursing homes tend to be more independent in carrying out their daily activities. The impact of the fall on the elderly is resulting in various types of injurien, physical and psychological damage. This study aimed at determining the correlation between the level of independence and the tisk of falling in the elderly. This study used analytic survey with the cross-sectional design. The population of this study was all elderly at Darma Bhakti Nursing Home KM. 7 Palembang. 31 respondents were selected as samples of this study by using the total sampling technique. The data collection instruments were observation sheets and questionnaires. The data collection instrumens were observation sheets and questionnaires. The data were analyzed by using the Kendall Tau test.The results revealed that the majority of respondents (71.0%) were> 70 years old, the majority of sexes were women (74.2 %), the majority of the levels of independence were dependence (51.6%), and the majority of the risk of falling was high with 22 respondents (71.0%). The Kendall Tau Test result showed there was a significant correlation between the level of independence and risk of falling (r = 0.504; p-value = 0.005). Conclusion: there is a retionship between the level of independence with the risk of falling in the elderly at the nursing home darma bhakti km 7 Palembang.from those result, it was expected that the board of directors should pay more attention to the programs that had been implemented and improve the falling risk prevention education to anticipate recurring falling in the elderly.Keywords: The Level of Independence, Risk of Falling.